Climate Risk Profile for East Africa - Demissie, Teferi; Gebrechorkos, Solomon; Radeny, Maren A.O.; Solomon, Dawit (International Livestock Research Institute, 2025)
The East African region, a vibrant hub of agricultural activity and rich biodiversity, stands at the forefront of the global climate crisis. As evidenced by the escalating frequency and intensity of hydroclimatic extremes such as floods and droughts, climate change and variability pose an existential threat to the livelihoods of millions and the region's sustainable development. Agriculture, predominantly rainfed and supporting over 80% of the population and the vital livestock sector, is acutely vulnerable to these shifting climatic patterns. This Climate Risk Profile for East Africa, a collaborative effort between the International Livestock Research Institute (ILRI) and the University of Oxford, aims to provide comprehensive and actionable insights into the region's current and future climate challenges. Building upon the foundational knowledge presented in the State of the Climate in Africa reports series, this document delves deeper into the specific climate risks impacting the water, agriculture, livestock, and ecosystem sectors across Ethiopia, Kenya, Uganda, and Tanzania. Our collective understanding, reinforced by the latest scientific data and validated climate models, underscores the urgent need for robust adaptation strategies. The State of the Climate in Africa 2024 report highlighted that 2024 was among the warmest on record for Africa, with sea-surface temperatures reaching new highs and significant temperature increases across all subregions, including East Africa. This warming trend, highly variable precipitation patterns, and increasing extreme events directly impact food security and water availability. The tragic events of 2023, such as the Borena Zone drought in Ethiopia, which devastated livestock, and the severe flooding in Kenya and Tanzania during 2024, serve as stark reminders of the immediate and devastating consequences of the region's vulnerability to climate extremes. This profile integrates high-resolution historical climate data with projections from selected Global Climate Models (GCMs) under various Shared Socioeconomic Pathways (SSPs). It provides detailed analyses of seasonal and annual climate changes and potential impacts on key sectors and proposes general policy recommendations, emphasizing the development of site-specific adaptation measures. We believe this profile document will be a crucial resource for policymakers, researchers, development partners, and local communities in East Africa. By fostering a deeper understanding of the evolving climate risks and promoting an integrated, multi-sector governance approach to adaptation, we can collectively work towards building a more resilient and food-secure future for the region. The commitment to strengthening technical and institutional capacities, facilitating financial and technical support, and sharing knowledge and guidance is paramount in this endeavor.